2013
DOI: 10.5267/j.esm.2013.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Determination of permissible defect size for solid axles loaded under fully-reversed rotating bending

Abstract: The aim of the present work was to develop a guideline for approving the railway axles made of C35 steel and containing surface and/or in-body defects after manufacturing. First, several through and part-through circular cracks were modeled on the surface and in the body of the axle at its critical cross-section. Then, the permissible size of such cracks was determined by using the fracture mechanics. To verify the validity of the guideline, the theoretical result for the semi-circular surface crack was compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…While the fatigue strength problem at low and high temperature has been investigated in a number of papers and books (Ko & Kim, 2012;Liu et al, 2013;Prasad et al, 2013, Torabi & Aliha, 2013) (see also References reported therein) as well as the modeling of materials subjected to high temperature inelastic behavior has been studied in recent contributions, the number of works dealing with copper alloys is limited and, in particular, no papers discuss the fatigue behavior at elevate temperature of notched specimens made of Cu-Be alloys.…”
Section: Introductionmentioning
confidence: 99%
“…While the fatigue strength problem at low and high temperature has been investigated in a number of papers and books (Ko & Kim, 2012;Liu et al, 2013;Prasad et al, 2013, Torabi & Aliha, 2013) (see also References reported therein) as well as the modeling of materials subjected to high temperature inelastic behavior has been studied in recent contributions, the number of works dealing with copper alloys is limited and, in particular, no papers discuss the fatigue behavior at elevate temperature of notched specimens made of Cu-Be alloys.…”
Section: Introductionmentioning
confidence: 99%
“…Since the critical distances of sharp crack for the MTS and MS criteria are normally assumed to be the material properties, they have been frequently used also for notches of different shapes (Ayatollahi & Torabi, 2010a, 2010bTorabi, 2013d;Torabi et al, , 2014dTorabi & Amininejad, 2015aTorabi & Aliha 2013;Torabi & Pirhadi 2015;Torabi & Abedinasab, 2015a. For U-shaped notches, the critical distances can be written as …”
Section: Computing the Critical Distances Of Umts And Ums Criteria Fomentioning
confidence: 99%
“…The crack can initiate from the surface or at a depth below the surface depending on the material processing conditions or from the stress concentrators such as pre notches, cracks, holes and etc. (Torabi & Aliha, 2013). Fatigue test using constant amplitude loading is a commonly practiced to predict the fatigue life properties of materials.…”
Section: Cae Fatigue Life Prediction By Ansysmentioning
confidence: 99%